Markerless biomechanical analysis of former elite rhythmic gymnasts - Mendelson, N.; Yona, T.; Peleg, S.; Ravina, O.; Fischer, A. (ISBS Proceedings Archive: Vol. 42: Iss. 1, 2024)
This study addresses the critical gap in understanding the biomechanics of key rhythmic gymnastics elements with high loads on the feet and ankles, specifically Fouetté balance and turns. These elements require repeated plantar and dorsiflexion movements. The study analyzed the forces and ankle sagittal angles of four former elite gymnasts using markerless motion capture and force plates. We segmented each movement into distinct biomechanical phases, particularly in 'Relevé' and Plié positions. Higher forces were observed during the Fouetté turn, and higher plantarflexion angles were found during the Fouetté balance. To the authors best knowledge this is the first study to segment and quantify common movements in rhythmic gymnastics, offering potential benefits for enhancing rhythmic gymnastics specific training and rehabilitation programs.